A Criticism of the Current Legal Science of Iran from the Perspective of Islamization with Emphasis on Civil Law - Mohammad Mahdi Alsharif; Nasrollah Jafari (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
It has been several decades since the concern of Islamization and localization of humanities has occupied the mind and conscience of the country's cultural custodians. Among the humanities, mostly imported sciences such as psychology, which have Western origins, have been considered for localization and Islamization discussion. Based on a superficial conception, considering that the primary codes, such as the Civil Code, are adapted from jurisprudence, we are not facing the challenge of Islamization in legal science. This conception is incorrect for multiple reasons. In the field of law, we face challenges in the two domains of legislation and interpretation. In the area of legislation, one of the fundamental challenges is the existence of a vast volume of laws related to the time before the revolution in which legitimacy has not been audited, and the most important challenge is related to the interpretation system. The existence of some religious propositions and even the establishment of laws based on Islamic principles are not enough for forming Islamic legal science, and the importance lies in the viewpoint and method of interpreting and developing these propositions based on Islamic principles. In this research, we deal with the pathology and criticism of the current legal science, emphasizing civil law as one of the main branches of legal science, in the two fields of legislation and interpretation, based on the descriptive and analytical method from the perspective of Islamic jurisprudence.